THE EFFECT OF REVENUE ON CAPITAL EXPENDITURE, INFRASTRUCTURE FINANCING, GOVERNMENT ACCOUNTABILITY PERFORMANCE SYSTEM AND BUDGET REFOCUSING IN CENTRAL JAVA PROVINCE DURING PANDEMIC - Desy Meliawati; Novi Dirgantari; Eko Hariyanto; Bima Cinintya Pratama (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The COVID 19 pandemic has an effect on regional income and expenditure in Central Java Province. One of the efforts made by the government is to refocus the budget aimed at Emergency Spending. The purpose of this study is to test the Effect of Locall Revenue (PAD) on Capital Expenditure, Infrastructure Financing, Accountability Performance System and Budget Refocusing. The research method used is quantitative. The sampling technique used was saturated samples and obtained data on 35 districts and cities in Central Java. Data analysis techniques use GLM Manova analysis. Theoretically, this study offers a new research model to explain effect Local Revenue to Capital Expenditure,Infrastructure Financing,Accountability Perfomance and Refocusing. The results of this study show that the variable of Local Revenue has a negative impact on Capital Expenditure, Infrastructure Financing, Government Accountability System,while Local Revenue has positive impact on Budget Refocusing. Theoretically, this study offers a new research model to explain effect Local Revenue to Capital Expenditure,Infrastructure Financing,Accountability Perfomance and Refocusing, because the government of each region can manage PAD even though it is less than optimal so it tends to have low Capital Expenditure. By the decrease in Local Revenue, it has implications for Local Revenue contributed to Capital Expenditure, Infrastructure Financing, Accountability Performance and Budget Changes. In this study, Local Revenue contribute to Capital Expenditures including infrastructure and Budget Changes. Keywords: Local Revenue,Capital Expenditure,Infrastructure Financing,Accountability Performance, Refocusing